Akha zangr : the Akha system of sustainable development and its conflicts with Thailand's development process : a thesis presented in partial fulfillment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University - Phillips, Emma (Massey University, 2003)
This thesis assesses Akha "zangr" ("way of life") as an indigenous system of development relevant to Akha development in the highlands of Thailand. It uses the principles of sustainable development studies, incorporating empowerment, gender, environment, health, education, justice, equality, poverty and participation as a framework for the assessment. This is the first study to examine Akha zangr as a system of sustainable development. It follows on from the description given by Alting von Geusau (1999) of Akha zangr as a "system for the sustainability and continuity of the Akha as a margnialised people". It is an attempt to empower the Akha community by giving credit to their knowledge and system of development as a modern rather than traditional system relevant to the 21st century. In Thailand there are nine ethnic groups officially recognised as indigenous to the highlands, each with a unique language and "zangr" based on strategies for survival and development in the highland environment. This thesis describes their common experiences of the Thai development process. Consequences include political and social exclusion from participation in the development process, their unjustified label as "problem makers" in Thai politics, and the inaccurate assessment of Mountain People as ignorant and backward. Disastrous impacts of foreign development in the highlands include deforestation, poverty, human rights abuses and a loss of cultural independence and knowledge for minority ethnic groups. Thailand's development process is examined based on increasing economic growth. Discussions focus on the industrialisation period initiated in the 1950's until the present day that, on paper, closely follow trends in international development thought. Thailand's policies of sustainable development have so far been ineffective in reducing environmental degradation from rapid economic growth and instead exclude local people from participating in the management of the environment. The assessment concludes that Thailand's top-down national economic growth policies have failed to improve the quality of life for the most disadvantaged people in Thai society and instead have caused massive environmental degradation, increased poverty, inequalities and the disempowerment of individuals and the community.
Keywords: Akha (Asian people) -- Thailand, Northern; Minorities -- Thailand, Northern; Sustainable development -- Thailand, Northern; Sustainable development -- Thailand; Thailand -- Economic policy